Antimicrobial Activity of Essential Oil of Baccharis dracunculifolia DC (Asteraceae) Aerial Parts at Flowering Period - Cazella, Luciane Neris; Glamoclija, Jasmina; Soković, Marina; Gonçalves, José Eduardo; Linde, Giani Andrea; Colauto, Nelson Barros; Gazim, Zilda Cristiani (Frontiers in Plant Science, 2019)
Baccharis dracunculifolia DC (Asteraceae) is a Brazilian native bush tree, and its leaf essential oil presents biological activity, but the antimicrobial activity of its aerial part and flower essential oil is unknown or little studied, mainly against agents that cause foodborne diseases. Thus, this study aimed to determine the chemical composition and evaluate the antimicrobial activity of the essential oil of B. dracunculifolia aerial part (leaf+flower). This essential oil was obtained by hydro distillation and its chemical composition was determined by gas chromatographer coupled to a mass spectrometer (GC-MS). The minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and minimum fungicidal concentration (MFC) of the essential oil was evaluated against eight bacteria and eight fungi using 96-well microtiter plates. The essential oil yield was 1.8 ± 0.07%, and spathulenol (27%) and trans-nerolidol (23%), both oxygenated sesquiterpenes, were the major compounds found among the 30 obtained chemical compounds. The essential oil presented bacteriostatic and bactericide activity, mainly against Staphylococcus aureus, Bacillus cereus and Pseudomonas aeruginosa, and also fungistatic and fungicide activity. However, its antibacterial activity was more effective than the antifungal one by using the essential oil at lower concentrations. Essential oil of B. dracunculifolia may be a potential alternative for food applications in order to reduce synthetic chemicals in a more sustainable food industry.